환자의 신약 접근성 강화 정책 제안 - 최유나; 이형기; Choi, Yoona; Lee, Howard (한국임상약학회지, 2021)
Objective: This study aimed to overview and assess the effectiveness of the policies and regulations that have governed new drug access in Korea, and to propose policies to enhance patient access to drugs, particularly for new innovative medicines. Methods: We approached drug access issues in two perspectives: approval lag (or availability) and reimbursement lag (or affordability). The issues were identified and evaluated through the review of literature, public documents, reports published by the government agencies and private organizations, and news articles. Results: To shorten approval lag, it is recommended to hire and train more reviewers at the Ministry of Food and Drug Safety. Increasing user fees to a realistic level can facilitate this process. To reduce reimbursement lag, flexible incremental cost-effectiveness ratio threshold, alternative cost-effectiveness evaluation, and establishment of funding source other than the national health insurance are identified as the areas to be improved. Conclusion: The current policies and regulations had to be supplemented by new systems to drastically promote patient accessibility to new drugs, consequently in order to promote national public health.